Do Political Factors Influence U.S. Crude Oil Imports? - Beckman, Jayson; Nigatu, Getachew (International Journal of Energy Economics and Policy, 2021)
This work uses a gravity model to estimate the determinants of U.S. crude oil imports, introducing two variables tied to the political nature of trade: U.S. arm sales and the level of political freedom in a country. Model results indicate that contiguity is important for U.S. crude oil imports, but trade agreements are not. Being an OPEC member leads to more exports of crude oil to the U.S. These factors combined with the negative relationship with freedom and U.S. crude oil imports, suggests that the U.S. imports a lot of oil from countries that have little cultural and political similarities. Keywords: oil, gravity, structural break, U.S., politics JEL Classifications: Q4, F1 DOI: https://doi.org/10.32479/ijeep.11238